CORRELATION OF SALIVARY FLOW RATE IN STUNTING CHILDREN TO DENTAL CARIES LEVEL The Overview of Elementary School Students in Sungai Tiung, Kecamatan Cempaka, Banjarbaru - Ade Putri Pratiwi; Rosihan Adhani; Ika Kusuma Wardani (Universitas Lambung Mangkurat, 2023)
ABSTRAKBackground: Stunting is a new issue that has a bad impact on nutritional problems in Indonesia because affects the physical and functional body of the child and increases children's morbidity. Banjarbaru has the highest prevalence of stunting at 5-12 age, number two in South Kalimantan with 12.32%. Previous studies found stunting dental caries index is 8.23 with a very high category compared to normal children in 3.3, which is a moderate category. A poor salivary flow rate of more than 60 seconds has a very high DMF-T rate. Purpose: To Analyze the correlation of salivary flow rate in stunting children to the dental caries level at Elementary School Students in Sungai Tiung, Kecamatan Cempaka, Banjarbaru. Material and Method: This study used analytic observational research with cross sectional method. The sampling technique in this study was using probability techniques which were taken by cluster random sampling. The minimum number of samples in this study were 51 respondents, that determined with Numerical-Numerical Correlative Analytic samples formula. Results: The nutritional status of severe stunting group was 67.93% and the moderate stunting group was 32.07%. The average of salivary flow rate in stunting children was 0.09781 ml/minute which categorized in hyposalivation. The average def-t/DMF-T index in stunting children was 11.32, which is a very high category. The Spearman Correlation Test results obtained the result of sig value p = 0,000 (p <0.05) with the direction of the correlation -0.535 level of the strong category. Conslusion: There is a correlation between the average value of salivary flow rate in stunting children and the level of dental caries in Elementary School Students in Sungai Tiung, Kecamatan Cempaka, Banjarbaru.Keywords: Dental Caries, Salivary Flow Rate, Stunting.